The surprising costs of on-site surgical team CRM training: a Dutch example analyzed - Tessa L. Verhoeff; Jeroen J. H. M. Janssen; A. Eveline Röell; Reinier G. Hoff (Advances in Simulation)
Abstract Background Interprofessional team training is increasingly implemented in healthcare, especially in the acute care domain. Research shows a positive effect of Crew Resource Management (CRM) training on teamwork and non-technical skills, and there are indications that it might improve patient care. However, CRM training requires a lot of resources, time, and energy. There is a paucity of data on the costs of these programs. The objective of this study was to evaluate and categorize costs related to an in-situ CRM training program for surgical teams in the Netherlands. Methods An evaluation of costs was made for an in-situ CRM training program in the operating room (OR) in a tertiary academic center in the Netherlands. The program consisted of 20 half-day training sessions per year. Costs were evaluated for the year 2024. A distinction was made between costs and missed revenues due to not performing elective surgeries. Results Total costs of one half-day session added up to roughly €11.700-€15.700,of which 68–76% was due to missed revenues. The other major costs concern salaries of the participants, which made up 12–16% of the total cost of a training session. Conclusions In-situ CRM training in the OR is expensive, especially due to missed revenues. These costs need to be transparent to enable healthcare administrators to carefully allocate funds in their institutions. The costs of in-situ team training might balance against possible advantages in training quality due to the use of the actual clinical environment and to potential financial benefits through improved team performance. But this remains as yet unclear. (Quasi-)experimental studies are required to compare simulations on both patient or learner outcomes and financial aspects.